TANGGUNG JAWAB RUMAH SAKIT TENTANG KETERBUKAAN INFORMASI - Rifa’at Hanifa Muslimah; Gunawan Widjaja (Cross-border, 2022)
The provision of health services can be done anywhere. One of them is through the hospital. This study aims to analyze and explain the disclosure of information that must be conveyed by the hospital to the patient and the form of the hospital's responsibility for that information. The method used in this research is normative juridical. The data used are secondary data. The analysis was carried out qualitatively. The results of this study indicate the importance of information disclosure by hospitals to patients. The information conveyed includes not only what is regulated in laws and regulations but also internal hospital regulations known as hospital bylaws and special information related to specific patient requests or complaints.